2001
DOI: 10.1086/318871
|View full text |Cite
|
Sign up to set email alerts
|

[ITAL]Infrared Space Observatory's[/ITAL] Discovery of C[TINF]4[/TINF]H[TINF]2[/TINF], C[TINF]6[/TINF]H[TINF]2[/TINF], and Benzene in CRL 618

Abstract: We report on the detection with the Infrared Space Observatory (ISO), for the first time in the circumstellar medium, of the polyacetylenic chains C 4 H 2 and C 6 H 2 and of benzene (C 6 H 6 ) in the direction of the proto-planetary nebula CRL 618. Surprisingly, the abundances of di-and triacetylene are only a factor of 2-4 lower than that of C 2 H 2 . Benzene is Ӎ40 times less abundant than acetylene. We suggest that the chemistry in CRL 618 has been strongly modified by the UV photons coming from the hot cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 529 publications
(128 citation statements)
references
References 26 publications
1
121
0
2
Order By: Relevance
“…Adamantane may also be searched for in C-rich circumstellar envelopes, such as IRC+10216 or CRL618 where many small hydrocarbon molecules have already been identified. 46,47 Our work reports accurate transitions for 7 of the 11 IR active modes of adamantane but the three most intense bands are the CH stretching modes which could not be resolved in our work. To circumvent this problem, an experiment making use of the Jet-AILES apparatus is planned to record the jet-cooled absorption spectrum in the 3 μm region (see Cirtog et al 48 for a description of the Jet-AILES apparatus), which might be more appropriate for a potential detection in space using for example the high spectral resolution instruments available at the Very Large Telescope (see, e.g., CRIRES (Ref.…”
Section: Discussionmentioning
confidence: 64%
“…Adamantane may also be searched for in C-rich circumstellar envelopes, such as IRC+10216 or CRL618 where many small hydrocarbon molecules have already been identified. 46,47 Our work reports accurate transitions for 7 of the 11 IR active modes of adamantane but the three most intense bands are the CH stretching modes which could not be resolved in our work. To circumvent this problem, an experiment making use of the Jet-AILES apparatus is planned to record the jet-cooled absorption spectrum in the 3 μm region (see Cirtog et al 48 for a description of the Jet-AILES apparatus), which might be more appropriate for a potential detection in space using for example the high spectral resolution instruments available at the Very Large Telescope (see, e.g., CRIRES (Ref.…”
Section: Discussionmentioning
confidence: 64%
“…Vuitton et al (2007) and later Vuitton et al (2009b) showed significant abundances of polyynes (C2H2, C4H 2, C6H 2, C, H 2) in Titan's atmosphere at 1100 km using a photochemical model constrained by INMS ion measurements. In Vuitton et al (2007) they also note that the abundance for the higher carbon chain polyynes within Titan's atmosphere did not decrease as fast as that in other photochemical models (Yung et al, 1984;Toublanc et al, 1995;Wilson and Atreya, 2004), the ISM (MacLeod et al, 1984;Remijan et al, 2006;Cernicharo et al, 2001) and/or laboratory measurements (Coll et al, 1999) as the number of carbon atoms increased in the carbon chain. It is also well known, as discussed in Thaddeus (1994Thaddeus ( , 1994Thaddeus ( , 1995 and Vuitton et al (2007), that unsaturated polyynes can polymerize into long carbon linear chains from which fullerenes can form (Hunter, 1994;Thaddeus, 1994Thaddeus, , 1995.…”
Section: Fullerenes Versus Pahsmentioning
confidence: 73%
“…Several other new molecules have been detected in the envelopes around latetype stars and protoplanetary nebulae. Although not formally part of this review, the exciting SWS discoveries of C 6 H 6 (benzene), C 6 H 2 , C 4 H 2 (Cernicharo et al 2001a), and C 2 H 4 (Cernicharo et al 2001b) toward CRL 618 should be mentioned.…”
Section: New Detectionsmentioning
confidence: 99%